Direct Estimates for Certain Integral Type Operators (European Journal of Pure and Applied Mathematics, 2018)
In this note, we study approximation properties of a family of linear positive operators and establish asymptotic formula, rate of convergence, local approximation theorem, global approximation theorem, weighted approximation theorem, and better approximation for this family of linear positive operators.